2023
DOI: 10.1002/mco2.349
|View full text |Cite
|
Sign up to set email alerts
|

Signaling pathways in macrophages: molecular mechanisms and therapeutic targets

Ming Li,
Mengjie Wang,
Yuanjia Wen
et al.

Abstract: Macrophages play diverse roles in development, homeostasis, and immunity. Accordingly, the dysfunction of macrophages is involved in the occurrence and progression of various diseases, such as coronavirus disease 2019 and atherosclerosis. The protective or pathogenic effect that macrophages exert in different conditions largely depends on their functional plasticity, which is regulated via signal transduction such as Janus kinase–signal transducer and activator of transcription, Wnt and Notch pathways, stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 429 publications
(780 reference statements)
0
11
0
Order By: Relevance
“…Furthermore, the prediction of matrix metalloproteinase (MMP) inhibition, particularly MMP9, suggests a potential avenue for joint protection in RA [ 61 , 62 ]. Transcription factor NF-κB, a key regulator of inflammation, was targeted by several compounds, providing insights into potential anti-inflammatory effects [ 63 , 64 ]. Notably, the hydrazide of 2-hydroxyacetohydrazide stands out, possibly due to its unique structure.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the prediction of matrix metalloproteinase (MMP) inhibition, particularly MMP9, suggests a potential avenue for joint protection in RA [ 61 , 62 ]. Transcription factor NF-κB, a key regulator of inflammation, was targeted by several compounds, providing insights into potential anti-inflammatory effects [ 63 , 64 ]. Notably, the hydrazide of 2-hydroxyacetohydrazide stands out, possibly due to its unique structure.…”
Section: Resultsmentioning
confidence: 99%
“…However, treatment with 23-HBA effectively inhibited STAT6 protein phosphorylation. The JAK2 protein has been reported to be activated and phosphorylated upon IL-4 binding to its receptors, which leads to the recruitment of STAT6 and its phosphorylation [ 21 , 22 ]. Interestingly, we found that the phosphorylation of JAK2 protein induced by IL-4 remained unaffected by 23-HBA, suggesting that 23-HBA inhibited the phosphorylation of STAT6 protein through a JAK2-independent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…When IL-4 or IL-13 binds to the receptor, Janus kinase (JAK) is phosphorylated. This results in phosphorylation of tyrosine residues in the cytoplasmic region of the receptor, which provide multiple binding sites for the STAT6 molecule [ 21 , 22 ]. Once activated, STAT6 dissociates from the receptor to form a homodimer and enters the nucleus, where it binds to certain accessible DNA sequences, initiating the transcription of related genes and leading to the polarization of M2 macrophages [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on phenotype and function, macrophages are usually classified into M0 (inactivated), M1 (pro-inflammatory, classically activated macrophages) and M2 (anti-inflammatory, alternatively activated macrophages) phenotypes [46][47][48]. Among them, M1 macrophages highly express co-stimulatory molecules, such as major histocompatibility complex class II (MHC-II), CD68, CD80 and CD86, and other inflammatory factors, such as interleukin (IL)-1β, tumor necrosis factor (TNF), inducible nitric oxide synthase (iNOS) and interferon (IFN)-γ, which can activate other immune cells and promote inflammation [49,50]. In contrast, M2 macrophages phenotypically exhibit high expression of CD206 and CD163 and produce various cytokines, including arginase-1 (Arg-1), growth factors, angiogenic factors, and anti-inflammatory factors such as IL-10 and TGF-β, which negatively modulate immunity and promote tissue repair [51,52].…”
Section: Classification Characteristics and Preparation Of Macrophage...mentioning
confidence: 99%